Le corbusier visits bucharest and its environs. impressions from journey to the east (2006)
This article is about Le Corbusier’s impressions during his visit to Bucharest city and its outskirts, as part of the well known Journey to the East. It tells the adventures that took place at Le Corbusier youth in Bulgaria, from June 16th to 22nd, 1911. The author comments the teacher’s drawings and his more prominent findings: the popular houses in the city outskirts happened during the search of Greco paintings, presumed lost in the Carpatos. The author introduces us to the disappointment of the young Le Corbusier in front to the palaces of Bulgarian Kings, and the discovery of the exquisite sensuality of Bucharest’s women, as well as their elegant clothing that recalls him the Parisian fashion. Finally the author relates us the encounter of Le Corbusier with some of young and even consecrated local artists, and also the visit to the simple and eloquent monasteries of Caldarushani region. Without doubt, a significant journey that reveals the travels importance for the Swiss teacher.